Preventive and Corrective Predial Inspection and Maintenance: A Case Study in a Residential Building in Amazonas - Cordeiro da Silva, Lourival; dos Santos Mendonça, Viviane Cristiny; Bezerra de Lima, Igor; Barbosa de Alencar, David; Murrieta Vasconcelos Oliveira Bezerra, Camily (International Journal for Innovation Education and Research, 2019)
This article aims to describe the main manifestations found in the external area of ​​the residential building. The case study was performed through visual inspections of the structures, identifying the causes and proposing a correction method for these anomalies. Based on the literature review in books, articles, norms and laws, we sought to understand the definitions related to the inspection and preventive maintenance and corrective to the performance of the building, presenting the main points of interest using as reference the ABNT NBR 5674: 2012 - “Maintenance of buildings” and ABNT NBR 15575: 2013 “Performance of Housing Buildings”. After all the on-site survey was carried out, the intervention strategies were presented, ensuring that the facilities receive the necessary maintenance according to the needs of each environment. Therefore, it is concluded that the lack of maintenance in the residential building has caused discomfort in the residents and the expected performance for the building. Therefore, it is very important to have proper planning and conducting the building inspection throughout the building's life, and should have specialized and qualified professionals to perform preventive and corrective maintenance, so it will be possible to rescue its performance, ensuring durability, comfort and real estate appreciation.